An Anatolian Perspective for Lycian Art? Remarks on the Historiography of Lycian Art Studies (19th–21st Centuries AD) - Colas-Rannou, Fabienne (Actual Problems of Theory and History of Art, 2021)
Ancient Lycia was located in Southern part of Anatolia. Lycian art is mainly composed of sculpture, with an important corpus dating to between the 6th and the 4th centuries BC. Lycia was included in the Persian Empire from the middle of the 6th century BC to the conquest of Alexander the Great, and throughout this period maintained relations with the Ancient Greek world. Recent studies on Lycian art have enlightened the fact that an Anatolian background was ingeniously mixed with borrowings from Greek and Oriental visual cultures. Based on this Lycian example, the paper proposes to reflect on the contemporary perception of historiography. With a focus on carving style and iconography, it aims at developing three main themes: the impact of the 19th-century European cultural history on the reception of Lycian stone monuments and sculpture; the impact of traditional academic fields on the way of studying Lycian art; an emerging, new and broader perspective that restores importance to the Anatolian background. The two monuments that served us as a basis for our reflection are: the so-called “Harpy tomb” and “Nereid Monument” from Xanthos.
Keywords: Lycia; sculpture; iconography; cultural contacts; reception; historiography; Anatolia; Harpy Tomb; Nereid monument; Xanthos